THE INFLUENCE OF MICROLEARNING AND THE FLIPPED CLASSROOM MODEL ON PHYSICS LEARNING OUTCOMES OF SMK KESEHATAN TERPADU MEGA REZKY MAKASSAR - Nugraha, Wahyu; H, Nurhikmah; Febriati, Farida (JURNAL NALAR PENDIDIKAN, 2025)
This study examines the effects of Microlearning and Flipped Classroom, both individually and interactively, on physics learning outcomes at SMK Kesehatan Terpadu Mega Rezky Makassar. Using a quasi-experimental nonequivalent control group design, 69 students from four classes were involved. Data collection includes observation, tests, and documentation, analyzed through normality, homogeneity, paired t-test, and two-way ANOVA. Results show that microlearning with short videos significantly improves learning outcomes (p = 0.002) due to its concise and accessible material. The Flipped Classroom model also has a significant effect (p = 0.000) by promoting independent study and active classroom discussions. Two-way ANOVA indicates a significant interaction (p = 0.023) between both methods, with their combination yielding the highest learning improvement. This study concludes that both Microlearning and Flipped Classroom significantly enhance learning outcomes and interact positively to optimize student performance.